Characterizing Angler Preferences for Largemouth Bass, Bluegill, and Walleye Fisheries in Wisconsin. (28th June 2019) - Tingley, Ralph W.; Hansen, Jonathan F.; Isermann, Daniel A.; Fulton, David C.; Musch, Andrea; Paukert, Craig P.
Abstract: Managing recreational fisheries in lake‐rich landscapes with diverse fish communities and anglers alike presents a social and biological challenge for managers. Understanding angler preferences is central to navigating these challenges and can aid in predicting shifts in angler behavior in response to management actions or changing fish populations. Species‐specific angler surveys do not incorporate tradeoffs inherent in multispecies fisheries, thus limiting their application to real‐world management issues. To better understand angler preferences in relation to realistic tradeoffs among different fishing opportunities, we conducted a survey of Wisconsin anglers in 2013–2014 that included questions requiring anglers to choose between fisheries providing different outcomes. We used stated‐preference modeling to quantify angler preferences associated with Bluegill Lepomis macrochirus, Largemouth Bass Micropterus salmoides, and Walleye Sander vitreus fisheries. Next, we conducted a latent class analysis using survey responses to classify anglers into subgroups. Finally, we assessed the sensitivity of angler choice to changes in fishing opportunities. Results of the stated‐preference models indicated that both residents and nonresidents largely prefer "quality" (i.e., moderate catch rate and size structure) over "action" or "trophy" Bluegill fisheries and that characteristics of Largemouth Bass fisheries have more value to nonresidents than to residents. Aspects of the Bluegill fishery were most important in choosing among hypothetical lakes for resident respondents. Five angler subgroups were identified that show the importance of Bluegill and Walleye but shed additional light on anglers' commitment level and nonresidents' preference for Largemouth Bass. In addition, simulations of changes in Walleye, Largemouth Bass, and Bluegill fisheries indicated that maintenance of quality Bluegill fisheries is important to ensuring continued angler participation, while the retention of high‐yield Walleye fisheries is likely paramount to a subgroup of anglers. Our results offer insight into angler preferences across the lake‐rich landscape of Wisconsin and demonstrate how angler behavior may shift in response to transitions in fishing opportunities.